Transparency and Accountability of Village Fund Management - Junaidi, Dedy; Adnan, M. Fachri (Jurnal Ilmiah Ekotrans & Erudisi, 2023)
This Literature System Review seeks to assess the application of financial management principles, specifically transparency and accountability, in the management of state finances at the Village APBDes. The Elucidation to Law of the Republic of Indonesia Number 17 of 2003 on State Finances states that the overall objective of state financial management is to promote good governance in state administration. Therefore, state financial management should be conducted in a professional, transparent, and responsible manner, adhering to the fundamental regulations outlined in the Constitution. The extensive litigation surrounding the misappropriation of village finances by village heads and officials serves as a fundamental premise for this research. When discussing the state financial management system, it is essential to address the management of village funds. These monies are a component of state finances, and their utilization must be properly accounted for. Analysis of fiscal matters at the state level. To ensure the proper functioning of state activities, it is imperative for the government to establish a robust and transparent state financial administration system. This system should effectively prevent any instances of financial leakage, both in terms of revenue collection and expenditure management. State financial management refers to the comprehensive actions undertaken by state financial management officials in accordance with their position and power. These actions encompass planning, execution, oversight, and responsibility. The findings of the literature system review research indicate that in order to establish transparency and accountability in the management of village funds, it is necessary to have legal clarity, coordination and oversight, and community engagement. Additionally, this endeavor requires officials who possess competence and have access to suitable facilities.